Isokinetic strength test and functional outcomes in proximal humeral fractures treated with a locking plate - Costantino, Cosimo; Verdano, Michele Arcangelo; Jacopetti, Marco; Romiti, Davide; Lunini, Enricomaria; Pellegrini, Andrea; Ceccarelli, Francesco (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2014)
Background Despite the use of many shoulder outcome scales in subjects with rotator cuff pathology or instability symptoms, it can be problematic to select an instrumental evaluation in the shoulder trauma population. In this study we evaluated patients with proximal humeral fractures treated with internal fixation with a locking plate, analyzing the recovery of strength with an isokinetic test and its correlation with clinical and functional outcomes. Methods We enrolled 46 individuals (17 men, 29 women). The evaluation included a structured interview, measurement of ROM, isokinetic strength test and Constant-Murley and QuickDASH scores. The isokinetic test was performed in flexion/extension and external/internal rotation of the operated shoulder in comparison with the contralateral side and concentric contractions in all movements. The parameter tested was peak torque. Results In the operated shoulder values we noticed a statistically significant correlation between the QuickDASH and Constant-Murley score. QuickDASH showed a significant correlation with flexion isokinetic strength, partial correlation with extension isokinetic values and no correlation with external/internal rotation values. In addition, we found a correlation between the Constant-Murley score and all the isokinetic strength parameters. Comparing the operated shoulder and the contralateral, in Neer type 2 fractures there was no significant difference in all the isokinetic peak torque values; in Neer type 3 and type 4, there was a significant statistical difference in both flexion peak torque values and no significant difference in the other movements. Conclusions The isokinetic test can give objective data on strength recovery and could help the surgeonʼs clinical evaluation to assess the functional recovery of the operated shoulder over time. We believe that the isokinetic test and Constant-Murley score could act as a reference in the evaluation of post-surgical outcome of proximal humeral fractures. Furthermore, the type of fracture could be a post-surgical limb recovery predictor and the shoulder flexion force could be the best functionality recovery indicator.